Free-standing carbon nanotube film for high efficiency monopole antenna. (February 2022) - Song, Hyeonjun; Jeon, Hoyun; Im, Dasom; Çakmakçı, Nilüfer; Shin, Keun-Young; Jeong, Youngjin
Abstract: A flexible radio-frequency (RF) antenna allows wearable smart devices to have various functionalities. To develop a high-performance RF antenna, an outstanding radiation efficiency should be achieved. Metallic films are commonly utilized in RF antenna electrodes owing to their high electrical conductivity, which is related to the radiation efficiency. However, their high density and low mechanical stability under deformed states, such as the folding of metallic films, hinder their use as flexible RF antenna electrodes. In this study, we fabricated a carbon-nanotube (CNT) film via the direct-spinning method for use in a flexible RF antenna electrode. The network structure of the CNT film endows it with a high electrical conductivity and allows it to be freestanding without a polymeric binder. The freestanding CNT film-based RF antenna attained a high radiation efficiency of 85.6%, commercially useable level, and its performance remained stable even under mechanical deformation, such as bending and folding. This high performance is attributed to the network structure of the CNT film composed of pure CNT bundles. Graphical abstract: Image 1 Highlights: Carbon nanotube (CNT) film is used as a flexible electrode for RF antenna without any polymeric binder. The free-standing CNT film RF antenna attains a high radiation efficiency of 85.6%. The free-standing CNT film RF antenna shows stable performance even under mechanical deformation.